Attitudes and Preferences of People Aged 55 and Above for Seafood: Summary of Telephone Survey Results - Lisa House; Allen F. Wysocki; William A. Messina; Kathryn Olson (EDIS)
FE822, an 8-page illustrated fact sheet by Lisa House, Allen F. Wysocki, William A. Messina, Jr., and Kathryn Olson, presents a brief summary of information on consumer perceptions of seafood obtained from a 2008 survey to identify the attitudes and consumption behavior of consumers aged 55 and older for fish, shellfish, and aquaculture products. Published by the UF Department of Food and Resource Economics, April 2010.